Health Shocks and earnings trajectories: A comparative study of migrants and natives in Finland - Haider, Waseem; Salonen, Laura; Kilpi-Jakonen, Elina (Elsevier BV, 2026)
Objective
The earnings gap between migrants and natives is well-documented, but the extent to which health shocks contribute to this gap remains unclear. We estimated the impact of a health shock on long-term earnings for both natives and migrants from different regions of origin.
Methods
Using high-quality full-population register data, we followed all residents aged 25 to 58 years in 2011, who were employed and did not experience a health shock between 2011 and 2012. A health shock was defined as the unanticipated hospitalization in 2013–14. Annual earnings were followed from 2011 to 2018. Using an event-study approach, we estimated the average treatment effects on the treated using dynamic difference-in-differences models stratified by gender and region of origin.
Results
Health shocks led to substantial and persistent earnings losses. On average, the health shock reduced earnings levels by 7.4% for natives and 13.5% for migrants compared to their pre-shock earnings levels. Among migrants, significant declines were observed in earnings among those from European & Western, Russia and the former Soviet Union, as well as from ‘other’ region of origin. By gender, the earnings penalty due to health shocks was greater for migrant men (17.7%), 1.5 times that of their female counterparts (8.6%).
Conclusions
The overall migrant–native difference of about six percentage points was small. Even if the average earnings penalty of a health shock is similar across groups, health shocks could still contribute to migrant–native disparities if migrants are more likely to experience such shocks initially.